Narrative Communication of Urban Village Tourism in Yogyakarta for Governing Community Resilience - Yosi Septa Mutiarni; Zhafira Pinasthika (Indonesian Tourism Journal, 2025)
Tourism in urban village communities of Yogyakarta serves as both a livelihood strategy and a resilience mechanism for populations living in ecologically vulnerable areas such as the flood-prone Kali Code riverbank. Despite exposure to hazards including seasonal flooding, landslides, water pollution, and urbanization pressures, residents have transformed their settlement into a vibrant community-based tourism (CBT) destination rooted in cultural heritage, environmental stewardship, and social solidarity. This study aims to explore how the Kali Code community constructs tourism narratives and employs communication strategies to strengthen resilience, combat the stigma of slum living, and preserve local identity. Using a qualitative narrative methodology, data were gathered through direct observation, document review, and prior studies, analyzed to uncover themes linking tourism, identity, and resilience. Findings reveal that CBT in Kali Code is deeply participatory and bottom-up, integrating storytelling, heritage preservation, and environmental management such as waste sorting, greening projects, and hazard mitigation drills into its tourism activities. Communication operates as a strategic tool, with interpersonal dialogue, community events, and social media used to disseminate information, mobilize action, and engage visitors in the community’s transformation story. In contrast to more visually oriented, externally managed models like Jodipan’s Rainbow Village, Kali Code’s approach embeds promotion within local narratives of survival, pride, and collective agency. The study concludes that CBT, when grounded in participatory communication and local values, can simultaneously generate economic benefits, reinforce socio-cultural identity, and enhance adaptive capacity, offering a replicable model for urban communities facing environmental and social challenges.